SOCIAL ETHICS OF JAVANESE SOCIETY IN THE TRADITIONAL GAME OF BLARAK-BLARAK SEMPAL: A STUDY OF LITERARY SOCIOLOGY ETIKA SOSIAL MASYARAKAT JAWA DALAM PERMAINAN TRADISIONAL BLARAK-BLARAK SEMPAL: KAJIAN SOSIOLOGI SASTRA - Handayani, Dwi; Wulandari, Yosi (Universitas Andalas, 2025)
This study aims to describe the social ethics that exist in the traditional game of blarak-blarak sempal. The method used in the study is qualitative descriptive. Data collection uses literature studies. The data obtained were then analyzed using literary sociology theory. The result of this research is that there are various social ethics of the Javanese people in the traditional game of blarak-blarak sempal including the ethics of harmony, respect, mutual respect, and humility. The harmonious ethics are reflected when children join hands in games and sing blarak-blarak sempal songs together. The ethics of respect is reflected in the results obtained in the game. The ethics of helping each other is reflected when children help their friends who have fallen while playing. The ethics of working together is reflected when children work together to play games. And the ethics of humility are reflected when children win in the game and do not be arrogant towards other friends.